Efektivitas Pelatihan Kebersyukuran Terhadap Regulasi Emosi Pengasuh di Lembaga X - Zuanny, Iyulen Pebry; Karjuniwati, Karjuniwati; Barmawi, Barmawi; Rahmah, Siti (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
Institution X are non-profit organizations that provide alternative care for orphaned children. Institution X in Aceh shows complaints from agency managers and children, one of which is related to the ability to regulate the emotions of caregivers which ultimately has an impact on foster children. Therefore, this study aims to see the effectiveness of the effect of gratitude training on caregivers' emotion regulation. This study used a mix-method approach, namely quantitative methods using simple regression analysis and qualitative methods through observation, worksheets and evaluation. The subjects of this study consisted of 25 caregivers at Institution X in Banda Aceh and Meulaboh. The results of this study indicate an increase in gratitude training on emotional regulation with an increase in score of 1.24 points with posttest results (M = 72.24, SD = 6.60) higher than pretest (M = 71, SD = 6.11). This is reinforced by the magnitude of the contribution of gratitude to emotional regulation from the value of R2 = 0.081, which means that there is as much as 8% of the influence of gratitude on emotional regulation.